Spatializing Blackness : architectures of confinement and Black masculinity in Chicago - Shabazz, Rashad, 1976- (Champaign, IL : University of Illinois Press, 2015)
"This project traces how architectures of confinement, policing, surveillance, migration, and mass incarceration orient and imbue Black male bodies and gender performance with the stigmata of carceral punishment. As the northern city with the largest 20th century influx of southern Blacks, Chicago provides a powerful case study to understand how urban planning, architecture, crowded living quarters, surveillance, and policing function to regulate Black men's bodies. Rashad Shabazz makes an important contribution to the growing work on Black (bodily) geographies and the complex entanglements between the emergence of the US prison regime (and prison industrial complex) and the densely historical complexities of Black subjectivity formation. By first illustrating how Black men's geographies have been delineated throughout the twentieth century in Black Chicago in spaces such as interracial sex districts, cramped kitchenettes, segregated house project, and prisons, Shabazz is then able to analyze and generalize the impact this mapping has had on the formation of Black masculinity, Black cultural production, and Black men's health in Black spaces beyond Chicago. Shabazz employs various methods (history, sociology, and literary criticism), theories (poststructuralism and critical theory), and disciplines (human geography, critical race studies, gender studies, cultural studies, and epidemiology) to highlight the importance of the racialization of space, the role of containment in subordinating Black people, the politics of mobility under conditions of 'freedom, ' and to ultimately discuss how Black men resist spacial containment"--
"Over 277,000 African Americans migrated to Chicago between 1900 and 1940, an influx unsurpassed in any other northern city. From the start, carceral powers literally and figuratively created a prison-like environment to contain these African Americans within the so-called Black Belt on the city's South Side. A geographic study of race and gender, Spatializing Blackness casts light upon the ubiquitous--and ordinary--ways carceral power functions in places where African Americans live. Moving from the kitchenette to the prison cell, and mining forgotten facts from sources as diverse as maps and memoirs, Rashad Shabazz explores the myriad architectures of confinement, policing, surveillance, urban planning, and incarceration. In particular, he investigates how the ongoing carceral effort oriented and imbued black male bodies and gender performance from the Progressive Era to the present. The result is an essential interdisciplinary study that highlights the racialization of space, the role of containment in subordinating African Americans, the politics of mobility under conditions of alleged freedom, and the ways black men cope with--and resist--spacial containment. A timely response to the massive upswing in carceral forms within society, Spatializing Blackness examines how these mechanisms came to exist, why society aimed them against African Americans, and the consequences for black communities and black masculinity both historically and today"--
Preface: Geographic Lessons -- Carceral Matters : An Introduction -- Policing Interracial Sex : Mapping Black Male Location in Chicago during the Progressive Era -- "Our Prison" : Kitchenettes, Carceral Power, and Black Masculinity during the Interwar Years -- Carceral Interstice : Between Home Space and Prison Space -- "Sores in the City" : A Genealogy of the Almighty Black P. Stone Rangers -- Ghost Mapping : The Geography of Risk in Black Chicago -- Epilogue: Fertile Ground.
Includes bibliographical references (pages 141-153) and index.
Print version record.
Includes bibliographical references and index.
English.
eBooks on EBSCOhost
Keywords: African American men -- Illinois -- Chicago -- Social conditions -- 20th century; Masculinity -- Social aspects -- Illinois -- Chicago -- History -- 20th century; African Americans -- Illinois -- Chicago -- Social conditions -- 20th century; Architecture and society -- Illinois -- Chicago -- History -- 20th century; Space (Architecture) -- Social aspects -- Illinois -- Chicago -- History -- 20th century; Social control -- Illinois -- Chicago -- History -- 20th century; Imprisonment -- Social aspects -- Illinois -- Chicago -- History -- 20th century; Spatial behavior -- Social aspects -- Illinois -- Chicago -- History -- 20th century; Chicago (Ill.) -- Geography; Chicago (Ill.) -- Race relations -- History -- 20th century; Hommes noirs américains -- Illinois -- Chicago -- Conditions sociales -- 20e siècle.; Masculinité -- Aspect social -- Illinois -- Chicago -- Histoire -- 20e siècle.; Noirs américains -- Illinois -- Chicago -- Conditions sociales -- 20e siècle.; Architecture et société -- Illinois -- Chicago -- Histoire -- 20e siècle.; Espace (Architecture) -- Aspect social -- Illinois -- Chicago -- Histoire -- 20e siècle.; Contrôle social -- Illinois -- Chicago -- Histoire -- 20e siècle.; Emprisonnement -- Aspect social -- Illinois -- Chicago -- Histoire -- 20e siècle.; SOCIAL SCIENCE -- Gender Studies; SOCIAL SCIENCE -- Ethnic Studies -- African American Studies; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; Masculinity -- Social aspects; African American men -- Social conditions; African Americans -- Social conditions; Architecture and society; Geography; Imprisonment -- Social aspects; Race relations; Social control; Space (Architecture) -- Social aspects; Illinois -- Chicago; 1900-1999; Electronic book; History